Transformational Leadership: Women's Role in Building Competitive Integrated Islamic School - Kasman, Kasman; Setiadi, Fadlan Masykura; Zulfikar, Zulfikar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze the principal's strategy in overcoming obstacles such as gender stereotypes and patriarchal culture and its impact on the management of educational institutions into competitive integrated Islamic schools. The research method used is field research with a qualitative case study approach. Data were collected through interviews, observations, and documentation. Data were analyzed thematically to identify themes of women's leadership and patriarchal challenges and interpreted to understand their impact on school culture. The results of the study indicate that women's leadership in schools has shown extraordinary abilities in overcoming the obstacles faced, especially gender stereotypes and patriarchal culture. With an inclusive, participatory, and transformational leadership approach, the principal has proven her capability to manage educational institutions with solid vision, integrity, and commitment. This study contributes to the field of educational leadership by providing empirical evidence of the effectiveness of women's transformational leadership in the context of Islamic education, especially in overcoming gender-based challenges.